Chemical composition, in vitro cytotoxic and anticholinesterase activities of flower extracts of Senna spectabilis var. excelsa and Senna macranthera - Franca, Maria G. A.; Pessoa, Cláudia O.; Trevisan, Maria T. S.; Paiva, Cristiane F.; Lima, Daniele R.; Sousa, Anderson F.; Oliveira, Fátima C. E.; Cavalheiro, Alberto J. [UNESP]; Silva, Maria G. V. (Taylor & Francis, 2021)
In this study, we investigated the phenolic and antioxidant content, cytotoxic, and anticholinesterase activities of flower extracts of Senna spectabilis var. excelsa and Senna macranthera. The antioxidant activities performed by the DPPH and ABTS methods showed that the extracts possess good antioxidant activity, with emphasis on the S. macranthera extract, which obtained results very similar to the rutin pattern. In the evaluation of the cytotoxic activity, the species S. spectabilis var. excelsa presented expressive cytotoxicity against the cellular lines PC3 and HL60 with IC50 values 21.08 and 31.37 μg mL−1, respectively. The results of anticholinesterase activity showed that both the plants induced enzyme inhibition, reaching 14 mm of inhibition in the case of S. spectabilis var. excelsa. The good results obtained in this work may be related to the presence of compounds such as apigenin-7-apioglucoside, quercetin 3,4'-diglucoside, cassine and spectaline identified in the extracts in our previous work.
Keywords: acetylcholinesterase; antioxidant; cytotoxicity; Senna